Electron flow boosted highly selective ammonium production from microbial nitrate reduction - Chunlei Liu; Hanrui Zhang; Zhongrui Guo; Liping Jiang; Longbin Yu; Chao Zhu; Guibing Zhu (Water Research, 2026)

Elevated water levels drive greenhouse gas mitigation in the riparian zone profile - Qingbang Du; Ruiliang Xu; Yu Qin; Xinchen Cai; Chunhui Zhan; Ziman Song; Longbin Yu; Zhaowen Wang; Chenyu Li; Ziyang Tang; Yifei Li; Shanyun Wang; et al. (Journal of Environmental Management, 2026)

Mineral phase transformation drives molecular fractionation of dissolved organic matter during organic acid-driven weathering of bauxite residue - Chenglong Lu; Songlin Wu; Fang You; Dingyi Yu; Jitraporn Vongsvivut; Annaleise Klein; Lars Thomsen; David Parry; Ting-Shan Chan; Longbin Huang (Chemical Geology, 2026)

High co-occurrence but low heterogeneity of virulence factors and resistance genes in farmland soil - Longbin Yu; Liping Jiang; Chunlei Liu; Shanyun Wang; Guibing Zhu (Journal of Environmental Sciences, 2026)

Microcurrent stimulation reactivates the electron transport chain to resuscitate ammonia-oxidizing bacteria from low-temperature stress - Ziyang Tang; Bangrui Lan; Longbin Yu; Chunhui Zhan; Nan Zhang; Zhaowen Wang; Ziman Song; Chenyu Li; Xinchen Cai; Shanyun Wang; Guibing Zhu (Bioresource Technology, 2026)

From inhibition to degradation: advances in highly selective targeting strategies for HPK1 - Longbin Yu; Rui Yan; Yashi Li; Huijie Wu; Zhe-Shan Quan; Xiaoting Li; Qing-Kun Shen (Molecular Diversity, 2026)

Strongly spatial-confined self-assembled monolayers for high-performance perovskite photovoltaics - Dongyang Li; Qiming Yin; Zhiwei Ren; Guihua Zhang; Jie Li; Qianyi Li; Yu Han; Sibo Li; Lihan Pang; Hao Xia; Guang Yang; Longbin Qiu; et al. (Science Bulletin, 2026)

Identification and molecular mechanism of tilapia skin-derived collagen peptides mitigating aging using zebrafish aging model - Ge Xu; Longbin Tan; Jiewen Tan; Wenzhu Zhao; Zhipeng Yu (Food Bioscience, 2026)

Quantifying the contribution of reactive nitrogen loss through anaerobic ammonium oxidation in global wetlands and oxygen minimum zones - Bangrui Lan; Shuci Liu; Shanyun Wang; Yanting Zhang; Longbin Yu; Chunlei Liu; Guibing Zhu (Journal of Environmental Sciences, 2026)

Comammox ammonia oxidization and N2O production in vadose and saturated zone soils - Shanyun Wang; Ruiliang Xu; Manyi Xiao; Jie Yu; Longbin Yu; Zihao Heng; Zhiyuan Li; Qingbang Du; Yuting Zhou; Yifei Li; Guibing Zhu (Water Research, 2026)

Oak pollen infrageneric classification-based winter temperature reconstruction since the marine isotope stage 5 in Southeast China - Yinning Tang; Lu Dai; Fei Gong; Junjie Yu; Jilong Wang; Weijian Zeng; Limi Mao; Zhongjing Cheng; Longbin Sha (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Production of γ-Valerolactone from levulinic acid via selected transfer hydrogenation pathway by FeAl-framework ZSM-5 supporting ZrO2 - Xiaozhou Chen; Hailong Tian; Longbin Deng; Shuaishuai Zhou; Xin Yu; Zongyuan Wang; Yusen Li; Yajie Tian (Chemical Engineering Journal, 2025)

An Improved Thermoeconomic Diagnosis Method: Applying to Marine Diesel Engines - Nan Xu; Longbin Yang; Yu Guo; Lei Chang; Guogang Zhang; Jundong Zhang (Journal of Marine Science and Engineering, 2025)
Thermoeconomic diagnosis methods are designed to identify faulty components and evaluate the economic implications of these faults. However, these diagnostic techniques often struggle to filter out interference from induced factors during the diagnosis process. When multiple components malfunction simultaneously, these methods may fail to effectively identify all the faulty components. To address these challenges, this article introduces an improved thermoeconomic diagnosis method that integrates the traditional diagnosis method with the operational characteristic curves of the components. This improved method facilitates a more precise differentiation between the impacts of faults on each component, categorizing them into intrinsic and induced parts. The intrinsic part arises from the component’s inherent failure, while the induced part results from interactions among different components or adjustments made by the control system. The improved method generates fault diagnosis indicators and economic assessment indicators based on this classification, allowing for the identification of faulty components and the evaluation of the economic consequences of these faults. The proposed method was tested on a MAN 6S50 MC-C8 diesel engine and validated under two real operating conditions, where multiple faults were intentionally introduced in various components. The results demonstrated that the new method accurately identified all faulty components within the marine diesel engine and assessed the economic impacts of these faults.

Diverse metabolism drives comammox in continental-scale agricultural streams: Important ammonia oxidation but low N2O production - Shanyun Wang; Manyi Xiao; Liping Jiang; Yucheng Jin; Yuting Zhou; Longbin Yu; Gawhar Armanbek; Manting Wang; Jingchen Ma; Guibing Zhu (Science of The Total Environment, 2024)

In silico identification and mechanistic evaluation of novel tyrosinase inhibitory peptides derived from coconut proteins - Wenzhu Zhao; Longbin Tan; Qian Zhang; Feng Chen; Zhipeng Yu (Food Bioscience, 2024)

Bi-directional association between outdoor or social activities and cognitive function: do the PM2.5 exposure catalyze the detrimental inactivity-poor cognition cycle? - Yuling Jiang; Yifei Wu; Yang Hu; Shaojie Li; Longbin Ren; Jingjing Wang; Mingzhi Yu; Rui Yang; Zhouwei Liu; Nan Zhang; Kejia Hu; Yunquan Zhang; et al. (Environmental Research, 2024)

Nodule Formation and Nitrogen Fixation in Acacia holosericea Plants Grown in Soil Admixed with Iron Ore Tailings - Lina Yu; Fang You; Songlin Wu; Zhaohua Lu; April Hastwell; Brett Ferguson; Longbin Huang (Journal of Soil Science and Plant Nutrition, 2023)